A cor da oração : sociabilidades e resistências na irmandade de São Benedito em Aracaju-SE - Oliveira Junior, João Mouzart de (2015)
The big question that I raise up in this dissertation is to think of the constitution and permanence of the brotherhood of Saint Benedict during the 20th century, as a collective organization of people that activate the claim religious and ethnic socialization. This research aims to analyze the practices of sociability and resistance present in brotherhood of Saint Benedict in Aracaju, State of Sergipe. I understand the ties of solidarity and the discourses of identity in the context of this brotherhood. Dialog also closely with issues relating to the theme ethnic-racial in religious contexts. With respect to the methodology, I used the articulation between research on file and direct observation. I divide this dissertation in three chapters, the first, I realize a bibliographic survey about the theme that emphasizes the studies about fraternities, the field of Anthropology and the discussion about religious practices. In the second and third chapter, delivery of an ethnographic approach emphasizing three modes of entry in the field, accompanied by interviews, first with the files where I did a search from the documentation of the brotherhood. The main documents found were the enrolment forms, the statute, the death records, a letter from the caretaker of the cemetery and the photos of the group. A second entry from the direct observation of the feast of St. Benedict, in the years 2013 and 2014, noting the aspects of sociability in this commemoration. The third entry is given in the form of space observation of the graveyard of the brotherhood. Thus, this dissertation addresses a facet little known about Aracaju: the world of brotherhoods of "black". I realized that the survival strategies of the brotherhood of Saint Benedict, the Catholic world aracajuano if retrogression on the basis of ethnicity. From the color reference that became a uniting factor of a religious group mostly recognized and self-declared blacks. I have noticed that the spaces of sociability of ethnic brotherhood of St. Benedict were composed by processions, by prestitos funeral and the festivities dedicated to the Holy One.